Investigating the Impact of Technological Distinctive Competencies and Information Technology Capabilities on Internet Entrepreneurship by Means of Innovation Capability - Ayough, Ashkan; Alemtabriz, Akbar; Tavanaei, Mohsen (AMC Indian Journal of Entrepreneurship, 2020)
In the information age, establishing an online business has become the most prevalent approach for entrepreneurship. Entrepreneurs with creative ideas have created websites which are now a part of people’s daily life. In addition to high financial turnover and considerable economical profits, these websites have changed the face of human life entirely. In this research we intend to investigate the impact of information technology and technological competencies on internet entrepreneurship and compare the extent of their effect. In this research, we try to present a new and unique model for explaining the relationship between internet entrepreneurship and information technology. To achieve this, a model has been provided which can be said to be the only model that investigates the relationship between internet entrepreneurship and technological distinctive competencies. The current research is a descriptive survey which has employed the questionnaire tool in order to gather the required information. Therefore, an authentic questionnaire has been designed and distributed among internet entrepreneurs who do all their activities including advertisement, marketing, and sales through internet. The statistical analysis was conducted on the 202 usable questionnaires using SmartPLS and SPSS software packages. The findings reveal that technological competencies and information technology have significant impact on internet entrepreneurship.